Post-pandemic building resilience: Building Information Modeling and green building integration - Karamoozian, Masood; Zhang, Hong (Journal of Civil Engineering and Management, 2026)
This research explores how Building Information Modeling (BIM), green building design, and post-pandemic resilience contribute to sustainable, healthy buildings. Although studies have explored BIM’s impact on green buildings, its role after COVID-19 remains largely unexplored. This study fills this gap through a “Green BIM post-pandemic square” taxonomy, integrating findings from a 1999–2024 literature review and BIM software evaluation. The taxonomy delves into project phases, green attributes, BIM features, and post-pandemic considerations to uncover links between BIM, green buildings, and post-pandemic cycles. It reveals how BIM enhances green design, construction, operation, and retrofitting. Additionally, BIM scrutinizes green building parameters such as energy efficiency and supply chain management. The study underscores BIM’s potential in sustainability, occupant health, and supply chain resilience through Green Building Evaluations (GBE). Ultimately, it synthesizes data to guide building researchers and practitioners, identifying gaps and suggesting future initiatives. Relevant journals and software are incorporated to provide comprehensive insights into the subject.